Apakah Discovery Learning dapat Meningkatkan Keterampilan Komunikasi Matematis Siswa? - Pratiwi, Aprilia Saputri Riski; Sari, Christina Kartika; Burhanudin, Bani Amin (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
To face the Information and Communication Technology (ICT) Era, students need to master 21st century skills. One of them is mathematical communication skills. It is very important for students to master mathematical communication skills because it will help them connect ideas and concepts with mathematical symbols. This research aims to improve mathematical communication skills through the discovery learning model. This research is classroom action research (PTK) which was carried out in three steps, namely pre-cycle, cycle 1, and cycle 2. The research data was collected through tests and observations. The data analysis techniques used include data reduction, data presentation, and concluding. The PTK results show that the discovery learning model can improve students' mathematical communication skills in geometric transformation material. This is proven by obtaining a percentage result of 85% in mathematical communication skills, the indicator of presenting mathematical information or ideas with other forms of representation, and the indicator of composing arguments in solving mathematical problems in the last cycle phase. Apart from that, there was an increase in indicators of analyzing and evaluating mathematical thinking in mathematical communication by 75%.